2018
DOI: 10.1111/cen.13844
|View full text |Cite
|
Sign up to set email alerts
|

Total and high‐affinity corticosteroid‐binding globulin depletion in septic shock is associated with mortality

Abstract: Low circulating haCBG concentrations are associated with mortality in septic shock. These results are consistent with an important physiological role for haCBG in cortisol tissue delivery in septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
2
16
0
2
Order By: Relevance
“…Our previous human studies have demonstrated that a lack of targeted delivery of natural cortisol and/or administered hydrocortisone to damaged tissue is related to deficient serum concentrations of CBG, which perpetuates organ failure and death in sepsis. 13,14 To further probe the action of CBG in the finely tuned delivery of cortisol and other steroids, we developed a novel ligand binding assay. The chosen SPR technology provided a reproducible and readily applicable, direct ligand binding assay to quantitate the bimolecular interaction between recombinant CBG and a library of 19 steroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous human studies have demonstrated that a lack of targeted delivery of natural cortisol and/or administered hydrocortisone to damaged tissue is related to deficient serum concentrations of CBG, which perpetuates organ failure and death in sepsis. 13,14 To further probe the action of CBG in the finely tuned delivery of cortisol and other steroids, we developed a novel ligand binding assay. The chosen SPR technology provided a reproducible and readily applicable, direct ligand binding assay to quantitate the bimolecular interaction between recombinant CBG and a library of 19 steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has revealed falling serum haCBG concentrations over time in proportion to septic shock severity and lower haCBG levels is associated with septic shock mortality. 13,14 In sepsis and septic shock with attendant multi-organ failure and hepatic dysfunction, protein glycosylation does not increase, thus it is unlikely that the reduction in 9G12 reactive CBG is due to an increase in CBG glycosylation of the RCL in these states. Furthermore, a loss in 9G12 reactive CBG correlates with rising free cortisol concentrations in sepsis and septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of high affinity corticosteroid binding globulin (CBG) has been proposed to be an important adverse mechanism in critical illness. 6 In the absence of intact CBG, the delivery of glucocorticoids to tissues might be severely impaired even in the presence of a high serum level of steroid.…”
Section: Please See Related Paper On Pages [374-382] Of This Issuementioning
confidence: 99%
“…The study also does not address whether other aspects of glucocorticoid signalling aside from serum cortisol levels might become dysfunctional in severe illness. Depletion of high affinity corticosteroid binding globulin (CBG) has been proposed to be an important adverse mechanism in critical illness . In the absence of intact CBG, the delivery of glucocorticoids to tissues might be severely impaired even in the presence of a high serum level of steroid.…”
mentioning
confidence: 99%